Yield and Water Productivity of Winter Wheat under Various Irrigation Capacities. (17th January 2019) - Araya, A.; Prasad, P.V.V.; Gowda, P.H.; Kisekka, I.; Foster, A.J.
Abstract: The Agricultural Production Systems sIMulator model validated in a prior study for winter wheat was used to simulate yield, aboveground crop biomass (BM), transpiration (T), and evapotranspiration under four irrigation capacities (ICs) (0, 1.7, 2.5, and 5 mm/day) with two nitrogen (N) application rates (N1, 94 kg N/ha; N2, 160 kg N/ha) to (1) understand the performance of winter wheat under different ICs and (2) develop crop water production function under various ICs and N rates. Evaluation was based on yield, aboveground crop BM, transpiration productivity (TP), crop water productivity (WP), and irrigation WP (IWP). Simulation results showed winter wheat yield increased with increase in N application rate and IC. However, the rate of yield increase gradually reduced with additional irrigation beyond 2.5 mm/day. A 5 mm/day IC required a total of 190 mm irrigation and produced a 5%–16% yield advantage over 2.5 mm/day. This indicates it is possible to reduce groundwater use for wheat by 50% incurring only 5%–16% yield loss relative to 5 mm/day. The TP and IWP for grain were slightly higher under IC of 1.7 mm/day (15.2–16.1 kg/ha/mm and 0.98–1.6 kg/m 3 ) when compared to 5 mm/day (14.7–15.5 kg/ha/mm and 0.6–1.06 kg/m 3 ), respectively. Since TP and IWPs are relatively higher under lower ICs, winter wheat could be a suitable crop under lower ICs in the region. Relationship between yield–T and yield–ET was linear with a slope of 15–16 and 9.5–10 kg/ha/mm, respectively. Editor's note : This paper is part of the featured series on Optimizing Ogallala Aquifer Water Use to Sustain Food Systems. See the February 2019 issue for the introduction and background to the series . Abstract : Research Impact Statement : This research provides opportunities to save irrigation water, enhance irrigation water productivity and yield of wheat grown under appropriate nitrogen management.